Advances in study of relationships between gene polymorphisms and manganese poisoning - Jiayu FU; Yan LI (环境与职业医学)
Occupational manganese poisoning is one of the most important occupational diseases in China, and it can cause different degrees of damage to various organs of the body, among which neurotoxicity is particularly obvious. Single nucleotide polymorphism (SNP) refers to the presence of two or more alleles of a gene in a population. This genetic variation may affect an individual's sensitivity to environmental toxins, and most cases may be caused by complex gene-environment interactions. Recent studies have shown that the pathogenesis of manganese poisoning is closely related to genetic polymorphisms, which can alter the body's susceptibility to manganese by affecting metabolism among other pathways. In this paper, we reviewed the relationships between genes related to oxidative stress, iron metabolism, neurotransmitter metabolism, zinc transporter, parkinsonism, DNA damage repair, calcium transporting ATPase type 2C member 2 and manganese poisoning, aiming to explore the key polymorphic genes affecting manganese poisoning and to provide genetic insights into the specific mechanisms of manganese poisoning caused by occupational exposure and its prevention and treatment.